THE EUROPEAN PUBLIC PROSECUTOR’S OFFICE: A theoretical analyse of the proposed regulation for establishment of a European Public Prosecutor’s Office - Oana – Măriuca PETRESCU (Challenges of the Knowledge Society)
Establishing a new European body, namely, European Public Prosecutor’s Office, could be described as one of the sensitive issues currently under discussion within the European Union, especially in the context of the serious economic crisis that hit in the last 5 years both the European Union and the national economies, as well as their difficult recovery. The author’s intention is to describe the events proceedings the discussions to regulate the possibility to establish this concept in the Treaty of Lisbon, including a theoretical analysis of the regulation proposed by the European Commission in accordance with Article 86 TFEU to establish this new body of the European Union having as main goal to investigate, prosecute and bring to justice those who commit criminal offences affecting the Union’s financial interests. The author’s conviction is that if agreed to be establish, this new body could change Europe’s judicial landscape, from various reasons. One of these reasons is that this new European Public Prosecutor’s Office will constitute a network of around 100 prosecutors in charge to investigate and prosecute suspects for defrauding EU funding programs.